The Effect of Four Square Step Exercise and Ankle Strategy Exercise on Improving the Balance of the Elderly in Aisyiyah Branch, West Palbapang, Bantul, Yogyakarta - Veni Fatmawati; Indriani (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Balance is the ability to maintain a central projection. Balance is needed to maintain position and stability when moving from one position to another. The result of balance disorders is falls and often leads to injury, disability, loss of independence and reduced quality of life. Physiotherapists play a role in providing interventions, one of which is four square step exercise and ankle strategy exercise. To determine the effect of four square step exercise and ankle strategy exercise on improving balance in the elderly. Methods: quasi-experimental with pre and post design in the elderly at PRA West Palbapang, Bantul. Measuring instrument with TUTG (Time Up and Go Test). Based on the age of 100% of the elderly Women, based on the age of 100% between the ages of 60-74 years, Based on the work of 20 elderly as housewives. Based on statistical tests to determine the effect of groups 1 and 2. From the TUGT test results obtained with a value of P = 0.034, it means that P <0.05 and Ha is accepted and Ho is rejected. So it is stated that the 2 interventions are equally beneficial in balance disorders. Four Square Step Exercise and Ankle Strategy Exercise have an effect on improving the balance of the elderly in the West Palbapang Aisyiyah Branch, Bantul, Yogyakarta.